Nigeria : Staff Report for the 2005 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
Nigeria's 2005 Article IV Consultation reports that the authorities made good progress in implementing their structural reform program. Given favorable terms of trade, gross international reserves are projected to increase substantially. The economy is expected to benefit from improved infrastructure and policy initiatives aimed at spurring non-oil GDP growth, and removal of distortions. The medium-term outlook hinges on the government's ability to consolidate the progress it has made in macroeconomic stability, strengthen public expenditure management, and progress significantly in implementing structural reforms.